Diagnosis and Management of Interstitial Lung Disease in Patients with Connective Tissue Diseases - Koslow, Matthew; Maleki-Fischbach, Mehrnaz; Keith, Rebecca C. (Case Reports in Rheumatology, 2021)
Interstitial lung disease (ILD) associated with connective tissue diseases (CTDs) is highly heterogeneous in its clinical presentation and course. The diagnosis and management of CTD-ILD require a multidisciplinary approach involving, at minimum, a rheumatologist, a pulmonologist, and a radiologist. Close monitoring of patients with CTD-ILD is important to enable early detection of disease progression and inform decisions regarding the initiation or escalation of pharmacotherapy. In the absence of guidelines regarding how CTD-ILDs should be treated, clinicians face difficult decisions on when to use immunosuppressant and anti-fibrotic therapies. The importance of a multidisciplinary and individualized approach to the diagnosis and management of CTD-ILD is highlighted in the three case studies that we describe in this article.